Analisis Literatur Integrasi Nilai-Nilai Akhlak dalam Pembelajaran PAI Berbasis Kearifan Lokal Pesisir untuk Siswa Sekolah Dasar - Nuriani Nuriani (Lembaga Pengembangan Kinerja Dosen, 2023)
This literature study aims to analyze and describe the integration of moral values ​​in Islamic Religious Education (PAI) learning based on coastal local wisdom for elementary school students. The focus of this study is to identify moral values ​​that are relevant to the lives of coastal communities, analyze strategies for integrating coastal local wisdom in PAI learning, and describe the potential for developing PAI teaching materials based on coastal local wisdom. The research method used is a literature study with a descriptive-analytical approach. The sources of research data are journal articles, reference books, curriculum documents, and relevant previous research results over the past ten years. Data collection techniques are carried out through identification, classification, and content analysis. The results of the study show that: (1) Moral values ​​that are relevant to the lives of coastal communities include gratitude for the gifts of the sea, honesty, cooperation, courage, patience, and responsibility for the environment; (2) The strategy of integrating local coastal wisdom in Islamic Religious Education learning can be done through the development of contextual teaching materials, experiential learning methods, and authentic evaluation; (3) The development of Islamic Religious Education teaching materials based on local coastal wisdom has the potential to increase the relevance of learning, strengthen local cultural identity, and facilitate the internalization of moral values ​​in elementary school students. This study concludes that the integration of moral values ​​in Islamic Religious Education learning based on local coastal wisdom is a relevant and potential strategy to be implemented in elementary schools in coastal areas, especially at SDN 007 Panipahan.